Electrical Properties of HfSe2 Single Crystals Grown by Chemical Vapour Transport Technique - RADHAKRISHNAN, K.; MOHANAN PILLA, K. (Asian Journal of Chemistry, 2010)
In the present work, an attempt has been made to concentrate upon the family of layered materials having a CdI2 type structure. Single crystals of hafnium di selenide (HfSe2) have been grown by chemical vapour transport (CVT) technique, with iodine as the transporting agent using a two-zone horizontal furnace. Electrical resistivity of the grown crystals were measured using two probe and four probe methods. The measurements showed that resistivity decreases with increase in temperature showing semiconducting behaviour. Activation energy of charge carriers were determined. Hall mobility, Hall coefficient and carrier concentrations were determined. All crystals were found to be of n-type conductivity. The electrical conductivity, Hall effect and their temperature dependence concludes the characteristic features of the semiconducting properties of these compounds.